KAJIAN PERSEPSI MAHASISWA TERHADAP LEMBAR KERJA MAHASISWA PADA MATA KULIAH PENDAHULUAN FISIKA ZAT PADAT - Darmaji, Darmaji; Berthalita Pujaningsih, Febri; Lestari Tambunan, Juni (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2022)
This study aims to determine student perceptions of Student Worksheets in the Introduction to Solid Substance Physics course. Using a mixed method research method between quantitative and qualitative methods and the type of research is explanatory sequential, which strengthens the results of quantitative data. The research subjects were 47 active students who had contracted the Introduction to Solid Substance Physics course in the Physics Education study program at Jambi University. The research instrument was distributing student perception questionnaire sheets and lecturer interview sheets to students. The data analysis techniques used for the quantitative method are descriptive statistics and qualitative methods based on Miles & Huberman. The results obtained after conducting the research revealed that students were dominant in the excellent category for understanding the learning of the Introduction to Solid Substance Physics course on Student Worksheets, and following the results of interviews with lecturers, namely student responses were excellent and able to improve skills in the learning process. The introductory course in Solid Substance Physics is a limitation of this study, and the results obtained on the Student Worksheet are only for students of the Physics Education study program. Thus, further research can expand the subjects to be studied so that the results obtained are varied and good